AIA Malaysia / Athirah Ayuni Rahmat - Rahmat, Athirah Ayuni (Faculty of Business and Management, 2023)
During my six-month as a practical training student at Account Payable team at AIA Operation Shared Services in Cyberjaya, I learned a lot of things. I gained experience with financial procedures such as handling invoices, coordinating with vendors, and reconciling payments. In addition, I enhanced my communication, teamwork, and organization of time abilities. I contributed to initiatives that improved the effectiveness of the accounts payable process. Overall, the internship was an excellent opportunity that strengthened my self- assurance and interest for pursuing a career in finance. I am appreciative of the AIA team's help and guidance, and I look forward to implementing my new skills in the future. I believe that I have done best in this industrial training in order to complete my Bachelor Degree.